2016 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM) 2016
DOI: 10.1109/ieem.2016.7798190
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation strategy for the of product configuration systems in engineer-to-order companies

Abstract: -This paper will address how to develop a strategy when developing and implementing product configuration systems (PCSs) in engineer-to-order (ETO) companies. PCSs are often gradually implemented especially where there are complex products and processes in order to break down the overall project and reduce risk. This highlights the importance of having an overall strategy to guide the long-term development and implementation of PCSs. In this paper, guideline for making the strategy are provided and supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Grafmüller et al (2018) addressed the issue of complex mass customisation product development, deriving a business model to employ within small-medium enterprises that aim to achieve successful mass customisation strategies by using 'solution spaces'. Also, recent studies (Cannas et al, 2020b;Haug et al, 2019aHaug et al, , 2019bKristjansdottir et al, 2017) explored possible applications of product configurators in ETO companies, the challenges that ETO companies can potentially face before, during and after implementation of product configurators and the possible actions to overcome these challenges.…”
Section: Design Automationmentioning
confidence: 99%
“…Grafmüller et al (2018) addressed the issue of complex mass customisation product development, deriving a business model to employ within small-medium enterprises that aim to achieve successful mass customisation strategies by using 'solution spaces'. Also, recent studies (Cannas et al, 2020b;Haug et al, 2019aHaug et al, , 2019bKristjansdottir et al, 2017) explored possible applications of product configurators in ETO companies, the challenges that ETO companies can potentially face before, during and after implementation of product configurators and the possible actions to overcome these challenges.…”
Section: Design Automationmentioning
confidence: 99%
“…Indeed, in ETO industries, companies traditionally offer a high degree of customization, and thus the role of the product configurator is to allow customers and salespeople to navigate the variety (Haug, Ladeby, and Edwards 2009). Furthermore, the product configurator can be used for supporting and, to some extent, automating the sales and engineering processes (Kristjansdottir, Shafiee, and Hvam 2017). Also, Hvam et al (2013) reported as an indirect consequence that implementing a product configurator worked as a catalyst for reducing product portfolio complexity, as unnecessary complexity became more apparent during the modelling process.…”
Section: Benefits Of Product Configurators In the Eto Industrymentioning
confidence: 99%
“…The configuration task can be described in terms of a pre-defined set of components, which are described by a set of properties (attributes) and their values, connections of the components (parts), and constraints to prevent infeasible configurations [4,26]. A PCS can be implemented both to support the end-user of the product and/or as an internal tool to increase efficiency by improving the dialogue with the customer and automating the generation of product specifications [1,5,15,17,27,28].…”
Section: Pcs and Product Structurementioning
confidence: 99%
“…The literature describes numerous benefits of implementing a PCS to support specification processes. A specification process can be defined as a process that is concerned with generating different product specifications (e.g., quotes, sales prices, bill of materials, CAD models), which normally involves employees from different departments [1,5]. Companies utilizing a PCS demonstrate better capability in terms of offering a variety of products, improving product quality, simplifying the customerordering process, and reducing the complexity of both processes and products, in addition to increased product profitability [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%